Magnetic Anisotropy and Spin‐Parity Effect Along the Series of Lanthanide Complexes with DOTA1. Issue 1 (3rd December 2012) - Boulon, Marie‐Emmanuelle; Cucinotta, Giuseppe; Luzon, Javier; Degl'Innocenti, Chiara; Perfetti, Mauro; Bernot, Kevin; Calvez, Guillaume; Caneschi, Andrea; Sessoli, Roberta
<x xml:space="preserve">Abstract</x> Spotting trends: Upon going from TbIII to YbIII centers in the complexes of the DOTA4− ligand, a reorientation of the easy axis of magnetization from perpendicular to parallel to the LnO bond of the apical water molecule is experimentally observed and theoretically predicted (see picture; SMM=single‐molecule magnet). Only ions with an odd number of electrons show slow relaxation of the magnetization.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>